2022
DOI: 10.3390/en15041539
|View full text |Cite
|
Sign up to set email alerts
|

National Culture and the Market Development of Battery Electric Vehicles in 21 Countries

Abstract: Electric vehicles (EVs) have become a symbol of the fight against climate change. However, in many countries, the market development of EVs is sluggish, and adoption rates greatly vary worldwide. This study examines the impact of Hofstede’s six dimensions of national culture on the development of the electric car market using sales data from 2019 and 2020 in 21 OECD countries. Results of (OLS) linear regression analyses show that uncertainty avoidance, individualism, masculinity, and indulgence have a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 104 publications
(136 reference statements)
1
14
0
Order By: Relevance
“…Research on the role of collectivism on consumers' intention to adopt electric vehicles is scant, and scholars have been calling for further study on the topic. Previous studies found mixed results: Dogan and Ozmen [26] and Novotny et al [27] found a positive relationship between collectivism and intention to adopt electric vehicles, while Ashmore et al [28] and Barbarossa and Pastore [29] asserted the effect is negative. Further study on the relationship between collectivism and intention to adopt electric vehicles is needed as suggested by Afroz et al [30] and Adnan et al [31].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Research on the role of collectivism on consumers' intention to adopt electric vehicles is scant, and scholars have been calling for further study on the topic. Previous studies found mixed results: Dogan and Ozmen [26] and Novotny et al [27] found a positive relationship between collectivism and intention to adopt electric vehicles, while Ashmore et al [28] and Barbarossa and Pastore [29] asserted the effect is negative. Further study on the relationship between collectivism and intention to adopt electric vehicles is needed as suggested by Afroz et al [30] and Adnan et al [31].…”
Section: Introductionmentioning
confidence: 94%
“…For people with low environmentalism, collectivism positively influences their intention to adopt a hybrid electric vehicle [26]. Novotny et al [27] stated collectivism as a culture orientation positively influences electric vehicle adoption through a cross-cultural study among 21 countries. Collectivism is also found to influence the intention to adopt an electric vehicle positively [19,73].…”
Section: Collectivism and Intention To Adopt Electric Vehiclesmentioning
confidence: 99%
“…A large-scale study by Novotny et al [42] (on a sample of 21 countries), based on Hofstede's concept of different cultural dimensions (power distance, uncertainty avoidance, individualism vs. collectivism, masculinity vs. femininity, long-term vs. short-term orientation, and indulgence vs. restraint) aimed to determine the impact of culture on EV adoption through its role in innovative and environmentally conscious behaviour.…”
Section: Background and Literature Review 21 Previous Research On Ev ...mentioning
confidence: 99%
“…This work focuses on personal vehicles. Some analysts use multi-national approaches to explore differences in ETV adoption [16]; here, the focus is on a detailed analysis of adoption in a single large national market (the U.S.).…”
Section: Introductionmentioning
confidence: 99%